Molecular devices: Caroviologens as an approach to molecular wires—synthesis and incorporation into vesicle membranes - Arrhenius, Thomas S. (1986)
Molecular wires, which would allow electron flow to take place between different components, are important elements in the design of molecular devices. An approach to such species would be molecules possessing an electron-conducting conjugated chain, terminal electroactive polar groups, and a length sufficient to span a lipid membrane. To this end, bispyridinium polyenes of different lengths have been synthesized and their incorporation into the bilayer membrane of sodium dihexadecyl phosphate vesicles has been studied. Since they combine the features of carotenoids and of viologens, they may be termed caroviologens. Vesicles containing the caroviologen whose length approximately corresponds to the thickness of the sodium dihexadecyl phosphate bilayer display temperature-dependent changes of its absorption spectrum reflecting the gel → liquid-crystal phase transition of the membrane. The data agree with a structural model in which the caroviologens of sufficient length span the bilayer membrane, the pyridinium sites being close to the negatively charged outer and inner surfaces of the sodium dihexadecyl phosphate vesicles and the polyene chain crossing the lipidic interior of the membrane. These membranes may now be tested in processes in which the caroviologen would function as a continuous, transmembrane electron channel—i.e., as a molecular wire. Various further developments may be envisaged along these lines.